Lateral growth rate control of GaAs on patterned substrates by CCl4 and CBr4 during MOCVD - Kim, SI; Kim, MS; Kim, Y; Hwang, SM; Min, BD; Son, CS; Kim, EK; Min, SK (ELSEVIER SCIENCE BV, 1997)
With supplying CCl4 or CBr4, which have been utilized as p-type dopant sources for carbon doped GaAs epilayers, the lateral growth rate of GaAs can be controlled during metalorganic chemical vapor deposition (MOCVD) growth. The lateral growth rate can be represented as a linear function of the CCl4 or CBr4 flow rate. On the other hand, the GaAs vertical growth rate is relatively insensitive to the CCl4 or CBr4 flow rate. While the maximum ratio of lateral to vertical growth rate by CCl4 is about 14, the value is increased up to 29 by using CBr4. With increasing growth temperature, the lateral growth rate increases, but it decreases at more elevated growth temperatures than 700 degrees C. The lateral growth rate increases with increasing V/III ratio, but at higher V/III ratio it shows a trend to saturation. The doping activity of CCl4 and CBr4 show a similar trend but in all cases the lateral growth rate increments by CBr4 are larger than those by CCl4.
Keywords: CHEMICAL-VAPOR-DEPOSITION; FACET EVOLUTION; PHASE EPITAXY; LASERS